Intermolecular rhodium catalyzed hydroacylation of allenes: the regioselective synthesis of beta,gamma-unsaturated ketones - Randell-Sly, H; Osborne, J; Woodward, R; Currie, G; Willis, M (2009)
A variety of β-S-substituted aldehydes undergo efficient and regioselective rhodium catalyzed hydroacylation reactions with 1,3-disubstituted and 1,1,3-trisubstituted allenes, to deliver β,γ-unsaturated ketone products. Regioselectivites are controlled primarily by steric factors. The reactions are catalyzed by the complex [Rh(dppe)]ClO 4. © 2009 Elsevier Ltd. All rights reserved.